RAGAM DIMENSI PEMBELAJARAN ILMU PENDIDIKAN AGAMA ISLAM: ( Studi Konseptual Dimensi Spiritual dan Material) - Miswari, Miswari (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2024)
Education is an important element in human life that requires serious treatment in various dimensions, namely the outer and inner dimensions. The birth dimension requires extensive and detailed techniques and handling. The inner dimension requires in-depth philosophical study. This article discusses various dimensions in the study of Islamic religious education in higher education. The success of implementing Islamic religious education is largely determined by the outer and inner dimensions. The inner dimension includes the formation of a foundation for understanding humans and their knowledge systems, while the outer dimension is the technical aspects that need to be prepared so that the objectives of implementing the Islamic religious education program can be achieved. This qualitative research uses literature related to the research subject as the main data source. The data was then analyzed systematically. The results of the research show that in the inner dimension, educational attention to the philosophical dimension needs to make the Al-Qur'an a foundation for knowledge that is approached through a variety of epistemologies of knowledge. Meanwhile, in the external dimension, the implementation of Islamic religious education must pay attention to the preparation of learning participants in line with community needs, set standards for learning institutions, and focus on deepening learning approaches and methods.